Median Nerve Repair Using Sural Nerve Grafting: A Case Report - Prasetyo, Eko; Oley, Maximillian C.; Tjungkagi, Ferdinan; Manuhutu, Yovanka N.; Sitorus, Edwin H. (Universitas Sam Ratulangi, 2024)
Peripheral nerve injuries (PNIs) have increased to nearly 2.8% of all trauma cases. It often occurs in the upper extremities, such as the median nerve. EMG can be used to confirm a PNI diagnosis. When continuity defects are present in the injured nerve, a nerve graft procedure may be indicated. The most common donor nerve for repair is the sural nerve. Different surgical options are available for the repair of PNI. We presented a 39-year-old woman whose left hand was cramping and did not fully clench. On physical examination, there was an irregular scar on the left arm 1/3 upper region. Sensory deficits were found in the distribution areas of the median nerve, from digiti 1 to 3 of the manus sinistra. EMG showed the lesion of the left median nerve, an axonetmesis was suspected. The patient was then treated with sural nerve grafting to the median nerve using fibrin glue. The postoperative result revealed improvement in hand function. Grafting sural nerve to median nerve using fibrin glue was rarely performed. According to several studies, nerve grafts usually used 6-0 sized synthetic, monofilament, non-absorbable polypropylene sutures. however, there was no difference in the results between fibrin glue and sutures, both have good outcomes. In conclusion, repairing of the median nerve injury using autograft (sural nerve) and fibrin glue can be an option to restore the function of the hand. Keywords: peripheral nerve injury; median nerve; sural nerve; nerve grafting